Microscopic insights into the role of dissolved organic matter on chloroquine phosphate retention by ferrihydrite: enhanced preservation of chloroquine and inhibition of phosphate adsorption - Li, Mengke; Lin, Shuangyi; Liu, Yun; Chen, Yuehui; You, Zhimin (Separation and purification technology, 2026)
In this study, chloroquine phosphate (CQP) was selected as the model pollutant and citric acid (CA) as a representative dissolved organic matter (DOM) to elucidate their influence and the underlying mechanisms of CQP preservation by ferrihydrite (Fh). Results showed that Fh exhibited negligible retention capacity for chloroquine (CQ). In contrast, with increasing C/Fe molar ratios, the CA-modified ferrihydrite (CA-Fhx) markedly enhanced CQ retention, with CA-Fh0.55 achieving a retention rate of up to 90 % within 45 min. Throughout a 30-day experimental period, the immobilization rate of CA-Fh0.55 remained stable at approximately 90 %. The interaction between CA-Fh0.55 and CQ was initially governed by electrostatic attraction, followed by complexation via CN coordination, hydrogen bonding and halogen bonding. However, the incorporation of CA onto the Fh surface via FeOC bonding suppressed ligand exchange reactions closely associated with surface Fe centers, thereby limiting the adsorption of PO43− released by CQP molecule dissolution on the CA-Fh0.55. Mechanistic analysis revealed that the binding of CA introduced oxygen-containing functional groups to the Fh surface, which exhibited strong affinity toward CQ. This study provided important insights into the interactions between DOM and minerals in the environment and shed light on the migration and transformation of organic pollutants in natural systems. The CQ molecule was initially attracted to the CA-Fh0.55 surface through electrostatic interactions. Subsequently, a coordination bond was formed between the carbon atom of the surface COOH group, which acted as an electron pair acceptor, and the nitrogen atom of the CQ molecule's amino group, which served as an electron pair donor. In addition, hydrogen bonding occurred between the hydrogen atom of the COOH group and the nitrogen atom of CQ, while halogen bonding was established between the oxygen atom of the surface OH group and the chlorine atom of CQ. After preferential retention of CQ molecules by CA-Fh0.55, the positively charged CQ species anchored on the surface gradually attracted free PO₄3− ions from the solution via electrostatic forces. [Display omitted] •The introduction of CA endows abundant oxygen containing functional groups to Fh.•CA-Fh0.55 showed excellent retention capacity toward CQ during a 30-days period.•CN coordination bond, hydrogen bond, and halogen bond promote retention process.•The FeOC bonds limiting PO₄3− immobilization on CA-Fh0.55.